A new species of Calamus (Calaminae, Calamoideae, Arecaceae) from Sulawesi, Indonesia - Henderson, Andrew; Iqbal, Moh.; Rusydi, Muhammad; Pitopang, Ramadhanil (Phytotaxa, 2018)
A new species of Calamus from eastern Sulawesi, Indonesia, is described and illustrated, and compared with similar species.